A STUDY OF THE EFFECTIVENESS OF GUIDANCE IN LESSON PREPARATION AND PRESENTATION ON PRACTICE TEACHING AND ACADEMIC PERFORMANCE OF STUDENTS - Ajmeri, Samir Dilipbhai (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Teaching practice constitutes a fundamental aspect of teacher education programs. To enhance the quality of the teaching-learning process, it is essential to critically analyze elements such as lesson planning, instructional organization, classroom environment, and learner psychology. This study employed an experimental research design to investigate the influence of structured guidance in lesson preparation and presentation on the practice teaching performance of student-teachers. The results demonstrated that participants who received guidance exhibited significant improvements in their confidence levels, communication abilities, and classroom management skills. They also demonstrated enhanced competence in conducting question-and-answer sessions and completing lessons within the allocated time. Furthermore, the study highlighted the importance of a well-structured and comprehensive lesson plan that integrates all key instructional components. Effective preparation and systematic rehearsal facilitated the development of pedagogical proficiency, contributing to an enriched teaching-learning experience. These findings emphasize the role of targeted instructional support in promoting reflective teaching practices and fostering professional growth among pre-service teachers.